Information Sources Used by Farmers of Bundelkhand Region (Indian Journal of Extension Education, 2016)
India still breathes in villages with the help of information sources. These sources play very important role in agricultural technology transfer among farming community. In Bundelkhand region of Uttar Pradesh the scenario of information use is differ as compare to other parts of India due to socio-economic and physico-geographical reasons. With this background a purposive study was conducted in all seven districts of this region. The study was based on 700 randomly selected farming respondents’ views. The results showed that respondents education, caste category. Farm size and occupation were significant to mass media exposure while age and family type having non-significant relation. Around 84 percent farmers were practicing only agriculture, 45.46 per cent comes under small holding and 56 per cent belong to backward class. Results also indicated that about 58 per cent farmers were unknown about agricultural innovation related source of information while only 43.10 per cent farmers were well known in which only 26.51 per cent farmers utilized source of information. In this region activity of public extension system was found poor in terms of input delivery, advisory & diagnostic services but first line technology transfer system maintained faith among farmers with poor reach ability and utilization of information. Farmers were consulting more to fellow farmers, relatives, neighbors, input dealers and co operative societies regarding technology transfer services. Results also showed poor information utilization performance of Krishi Vigyan Kendra print media, mobile, internet, Kisan Call Centre and form Farmers organizations.